A systems approach to small group interaction - Tubbs, Stewart L. (McGraw-Hill, 2007)
This book explores the myriad ways in which groups and teams can be used to help achieve successful results. Intended as a primary text for courses in group communication, this book is also used as a text in management, psychology, nursing, and education courses.